Large landslides in the Alpine valleys of the Giudicarie and Schio-Vicenza tectonic domains (NE Italy). Issue 3 (1st June 2021) - Viganò, Alfio; Rossato, Sandro; Martin, Silvana; Ivy-Ochs, Susan; Zampieri, Dario; Rigo, Manuel; Monegato, Giovanni
ABSTRACT: A comprehensive geomorphological and structural mapping of the largest landslides in the central-eastern Southern Alps (NE Italy) is presented. Their occurrence in this Alpine sector is discussed in relation with structural geological features (bedding and faults), which are largely conditioned by the Giudicarie and Schio-Vicenza regional fault systems. Tectonic rock damaging here coexists with high relief stored energy and active deformation, which is testified by present seismicity and cumulative earthquake moment release. Based on updated rock failure ages, slope activity is concentrated at 5-3 and 1 ka, as primarily enhanced by climatic and seismic controls. The analysis of predisposing and driving factors poses the question of present and future landslide hazards for these densely inhabited Alpine valleys.